The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/fpc.0b013e328330a39f
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment tumor gene expression signatures are more predictive of treatment outcomes than baseline signatures in breast cancer

Abstract: Postchemotherapy tumor gene signatures outperformed baseline signatures and clinical predictors in predicting for pathological response and PFS, independent of clinical and pathological response to chemotherapy. Drug-induced tumor gene signatures may be more informative than unchallenged signatures in predicting treatment outcomes. These findings challenge the current practice of relying only on the baseline tumor to predict outcome, which overlooks the contributions of therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…One to two core biopsies from the primary breast tumor were taken each at baseline and approximately 3 weeks after the first cycle of chemotherapy, snap frozen in liquid nitrogen and stored at -80°C until analysis. Only RNA was extracted from the first tumor core for gene expression analysis, the data of which has been reported previously [ 4 , 7 ], while both DNA and RNA was extracted from the second tumor core if available, for DNA mutational analysis and other RNA expression work. Bidimensional breast tumor assessments were performed at every cycle.…”
Section: Methodsmentioning
confidence: 99%
“…One to two core biopsies from the primary breast tumor were taken each at baseline and approximately 3 weeks after the first cycle of chemotherapy, snap frozen in liquid nitrogen and stored at -80°C until analysis. Only RNA was extracted from the first tumor core for gene expression analysis, the data of which has been reported previously [ 4 , 7 ], while both DNA and RNA was extracted from the second tumor core if available, for DNA mutational analysis and other RNA expression work. Bidimensional breast tumor assessments were performed at every cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Lee, et al demonstrated that postchemotherapy tumor gene signatures outperforms baseline signatures and clinical predictors in predicting for pathological response and progression-free survival [42], although these investigators collected posttreatment breast tumors 3 weeks after chemotherapy, not at the time of progressive disease as in our study. Our data is consistent with the aforementioned study [42] that comparing postchemotherapy and prechemotherapy gene expression signatures might be a feasible approach to the identification of predictive signatures. Also, our data provides the first genomic evidence in clinical samples supporting a conventional model for the emergence of acquired resistance whereby resistance emerges through a selective, clonal outgrowth of small populations of pre-existing, chemoresistant tumor cells [3].…”
Section: Discussionmentioning
confidence: 98%
“…No prior studies have explored acquired resistance using genome-wide analysis of clinical samples, although 2 prior studies evaluated the gene expression pattern in residual disease after the completion of neoadjuvant chemotherapy [40], [41]. Lee, et al demonstrated that postchemotherapy tumor gene signatures outperforms baseline signatures and clinical predictors in predicting for pathological response and progression-free survival [42], although these investigators collected posttreatment breast tumors 3 weeks after chemotherapy, not at the time of progressive disease as in our study. Our data is consistent with the aforementioned study [42] that comparing postchemotherapy and prechemotherapy gene expression signatures might be a feasible approach to the identification of predictive signatures.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, patients in Cohort B had fewer ductal carcinomas and, even more importantly, less frequently received neoadjuvant chemotherapy. Gene expression alterations of breast cancer were recently demonstrated to be drug-specific, and drug-induced tumor gene signatures may be more informative than unchallenged signatures in predicting treatment outcomes [ 18 , 19 ]. The study by Bos et al [ 20 ] showed that BM gene set tested in various breast cancer cohorts was less BM predictive in patients whom received postoperative systemic therapy compared to those whom did not.…”
Section: Discussionmentioning
confidence: 99%